Penerapan Laporan Keuangan Berdasarkan SAK EMKM Pada Usaha Sate Ayam Barokah - Annisa Puteri Ilham; Dinda Mustika Triwardani; Putri Adilla; Siti Rodiah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
One of the financial standards applied by DSAK IAI is the Financial Accounting Standard for Micro, Small and Medium Entities (MSMEs) which aims to change it become easy for MSE’s entrepreneurs to serve and compile it more simple about understanding the financial statement for investors and creditors, so that they can help provide financing to them. This condition occurs in MSMEs Sate Ayam Barokah, a culinary business located on Jl. Kaharuddin Nst, Simpang Tiga, Bukit Raya District, Pekanbaru City, Riau 28288, while the branch is located on Jl. Cipta Karya Panam, West Sidomulyo, Handsome District, Pekanbaru City, Riau 28293. This Sate Ayam Barokah MSME has long been established but until now it has not carried out accounting records and calculations in accordance with SAK EMKM. Therefore, this research’s goal is about to explore the financial statement’s preparation of SAK EMKM in the Sate Ayam Barokah Business. In conducting this study, a qualitative method is implemented here and the author collecting The conclusion here found that MSMEs of Sate Ayam Barokah do not apply accounting records at all according to SAK EMKM. The owner only calculates by subtracting the total income from the total working capital that has been spent in accordance with the owner's understanding.